Nanodiamond reinforced ultra high molecular weight polyethylene for orthopaedic applications: dry versus wet ball milling manufacturing methods. (March 2014) - Enqvist, E.; Emami, N.
<x content-type="archive" xml:space="preserve">Abstract</x> Nanodiamonds (NDs) were investigated as reinforcement for ultrahigh molecular weight polyethylene (UHMWPE). Dry and wet mixing with planetary ball milling was compared and analysed by scanning electron microscopy (SEM), differential scanning calorimerty (DSC), X-ray diffraction (XRD) and contact angle measurements. The composites were mixed from one to four hours to study the dispersion of the nanoparticles. It was concluded that wet mixing is more effective at distributing nanodiamonds in comparison to dry mixing. It could also be concluded that dry mixing increases the temperature by 20°C more than wet mixing which resulted in a more distinct welding process of the UHMWPE powder.